VRK1 Predicts Poor Prognosis and Promotes Bladder Cancer Growth and Metastasis In Vitro and In Vivo - Wu, Jiacheng; Li, Tao; Ji, Hao; Chen, Zhi; Zhai, Baoqian (Frontiers in Pharmacology, 2022)
Bladder cancer（BC）is one of the most common malignant tumors in the urinary system with growing morbidity and diagnostic rate recent years. Therefore, identify new molecular biomarkers that inhibit the progression of bladder cancer is needed for developing further therapeutics. This study found a new potential treatment target: Vaccinia-Related Kinase 1 (VRK1) and explored the function and mechanism of VRK1 in the development of bladder cancer. First, TCGA database and tissue microarray analysis showed that VRK1 was significantly up-regulated in bladder cancer. Kaplan-Meier survival analysis indicates that the OS and PFS of the VRK 1 high expression group were significantly lower than the VRK 1 low expression group (p= 0.002, p = 0.005). Cox multi-factor analysis results show that VRK 1 expression is an independent risk factor affecting tumor progress. The maximum tumor diameter, staging and adjuvant chemotherapy also have a certain impact on tumor progression (P <0.05). In internal validation, the Column C-index is 0.841 (95% CI 0.803-0.880). In addition, cell functional studies have shown that the VRK1 can significantly inhibit the proliferation, migration and invasiveness of bladder cancer cells. In vivo, nude mice transplanted tumors further prove that the low VRK1 can significantly inhibit the proliferation capacity of bladder cancer cells. In summary, VRK1 expression is significantly related to the staging, grade and poor prognosis of patients with bladder cancer. At the same time, in vivo and in vitro experiments have shown that down-regulation of VRK1 can significantly inhibit the proliferation of bladder cancer cells. These findings provide a basis for using VRK1 as a potential therapeutic target for patients with bladder cancer.